CORPORATE SOCIAL RESPONSIBILITY, LIQUIDITY AND LEVERAGE INFLUENCE ON FINANCIAL PERFORMANCE - Hidayati, Nurul; Indrianasari, Neny Tri; Yatminiwati, Mimin (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to examine the effect of Corporate Social Responsibility, Liquidity, Leverage and on Financial Performance in Manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019. This research uses secondary data from the financial statements Manufacturing company listed in Indonesia Stock Exchange. The sampling technique used is purposive sampling, with a sample of 45 companies for the 2017-2019 period. Based on the results of the study indicate that thevariable Corporate Social Responsibility, Leverage (Debt to Equity Ratio) has a significant effect on Financial Performance (Return On Assets), while Liquidity (Current Ratio) does not have a significant effect on Financial Performance (Return On Assets).